Pelvic pain in young girls: not only dysmenorrhoea!. (8th November 2018) - Veiga, Vera Furtado; Ribeiro, Barbara; Afonso, Hermínia; Reis, Isabel
Abstract : Imperforate hymen is the most frequent cause of haematocolpos, although it is a rare malformation (1:2000). We present two cases of young girls with cyclic abdominal pain and urinary symptoms. At gynaecological examination, they all presented imperforate hymen and ultrasound revealed significant vaginal distension. X-shaped hymenectomy was performed in all patients. The later the diagnosis of imperforate hymen, the higher the risk of complications like haematometra, haematosalpinx, haemoperitoneum and infections such as tubo-ovarian abscesses, peritonitis and endometriosis (retrograde menstruation theory).